نظرية الأحلام الفلسفية عند الفارابي - مبارك، نعيمة محمود مصطفى (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بكفر الشيخ, 2023)
تهدف هذه الدراسة إلى التعرف على نظرية الأحلام الفلسفية عند الفارابي، وبيان صلة الأحلام والرؤى بالنبوة، ولتحقيق هذا الهدف اتجهت الدراسة إلى تأصيل المسألة لدى أرسطو والكندي، وبيان مدى تأثير وتأثر في فكر الفارابي، فارتكزت الدراسة على إبراز الجوانب المتعلقة بمسألة الأحلام والنبوة عند الفارابي بصورة فلسفية مفصلة، لبيان حجية الرؤى والأحلام وصلتها بالنبوة عند الفارابي، قامت الدراسة على منطلقات علمية ومنهجية لفهم هذه المسألة. وقد تكون البحث من: مقدمة، وتمهيد، وثلاثة مباحث، وخاتمة: أما المقدمة: فذكرت فيها أهمية الموضوع، وأسباب اختياره، والمنهج المتبع، وخطة البحث. وأما التمهيد: ويشتمل على التعريف بالفارابي، والحديث عن معنى النظرية، ومعنى مصطلح الأحلام اللغوي والاصطلاح الفلسفي، وحديث القران الكريم والسنة النبوية عن الأحلام. وأما المبحث الأول: فتناولت فيه نظرية الأحلام عند أرسطو، والكندي. وأما المبحث الثاني: فتناولت فيه الحديث عن نظرية الأحلام عند الفارابي. وأما المبحث الثالث: فتناولت فيه بيان علاقة الأحلام بالنبوة عند الفارابي. وأما الخاتمة: فذكرت فيها أهم النتائج التي توصل إليها البحث. This study aims to identify the philosophical dream theory of al-Farabi, and to demonstrate the relationship of dreams and visions to prophecy. Detailed philosophical, to clarify the authenticity of visions and dreams and their connection to the prophecy of Al-Farabi, the study was based on scientific and methodological principles to understand this issue. The research consisted of: an introduction, a preface, three topics, and a conclusion: - As for the introduction: I mentioned the importance of the topic, the reasons for choosing it, the methodology used, and the research plan. As for the introduction: it includes introducing Al-Farabi, talking about the meaning of theory, the meaning of the linguistic and philosophical term dreams, and the hadith of the Holy Qur’an and the Sunnah of the Prophet about dreams. As for the first topic: I dealt with the dream theory of Aristotle and Al-Kindi. As for the second topic: I dealt with the talk about the dream theory of Al-Farabi. As for the third topic: I dealt with the explanation of the relationship of dreams to prophecy according to Al-Farabi. As for the conclusion: I mentioned the most important findings of the research.
Keywords: الفلسفة الإسلامية -- القرآن الكريم -- نظرية الأحلام -- الفارابي، محمد بن محمد، ت. 950 م